Nitric Oxide, Iron and Neurodegeneration - Liu, Chao; Liang, Mui Cheng; Soong, Tuck Wah (Frontiers in Neuroscience, 2019)
Iron is a crucial cofactor for several physiological functions in the brain including transport of oxygen, DNA synthesis, mitochondrial respiration, synthesis of myelin, and neurotransmitter metabolism. If iron concentration exceeds the capacity of cellular sequestration, excessive labile iron will be harmful by generating oxidative stress that leads to cell death. In patients suffering from Parkinson disease, the total amount of iron in the substantia nigra was reported to increase with disease severity. High concentrations of iron were also found in the amyloid plaques and neurofibrillary tangles of human Alzheimer disease brains. Besides iron, nitric oxide (NO) produced in high concentration has been associated with neurodegeneration. NO is produced as a co-product when the enzyme NO synthase converts L-arginine to citrulline, and NO has a role to support normal physiological functions. When NO is produced in a high concentration under pathological conditions such as inflammation, aberrantly S-nitrosylated proteins can initiate neurodegeneration. Interestingly, NO is closely related with iron homeostasis. Firstly, it regulates iron-related gene expression through a system involving iron regulatory protein and its cognate iron responsive element (IRP-IRE). Secondly, it modified the function of iron-related protein directly via S-nitrosylation. In this review, we examine the recent advances about the potential role of dysregulated iron homeostasis in neurodegeneration, with an emphasis on AD and PD, and we discuss iron chelation as a potential therapy. This review also highlights the changes in iron homeostasis caused by NO. An understanding of these mechanisms will help us formulate strategies to reverse or ameliorate iron-related neurodegeneration in diseases such as AD and PD.